Suicide Prevention Interventions and Their Linkages in Multilayered Approaches for Older Adults: A Review and Comparison - Sakashita, Tomoe; Oyama, Hirofumi (Frontiers in Public Health, 2022)
Multilayered approaches to suicide prevention combine universal, selective, and indicated prevention interventions. These approaches may be more successful in reducing suicide rates among older adults if they link these layers more systematically: that is, if the programs are designed so that interventions at a lower level facilitate involvement at a higher level when appropriate. This study aimed to examine the effect on suicide rates of the structure of multilayered approaches, and in particular the types of interventions and the connections or linkages between them. We also wished to consider any different effects by sex. A literature search used PubMed and PsycINFO to identify systematic reviews of interventions in this age group. From the reference lists of these articles, we identified controlled studies assessing the impact of a multilayered program on suicide incidence among older adults. We were particularly interested in initiatives linking different kinds of prevention interventions. We found three relevant systematic reviews, and from these, we identified nine eligible studies. These included seven non-randomized controlled studies from rural areas in Japan (average eligible population: 3,087, 59% women, average duration: 8 years). We also found two cohort studies. The first was from a semi-urban area in Padua, Italy (18,600 service users, 84% women, duration: 11 years). The second was from urban Hong Kong, with 351 participants (57% women) over a 2-year follow-up period. We used a narrative synthesis of these studies to identify five different multilayered programs with different forms of connections or linkages between layers. Two studies/programs (Italy and Hong Kong) involved selective and indicated prevention interventions. One study/program (Yuri, Japan) included universal and selective prevention interventions, and the final six studies (two programs in northern Japan) involved linkages between all three layers. We also found that these linkages could be either formal or informal. Formal linkages were professional referrals between levels. Informal linkages included advice from professionals and self-referrals. Several of the studies noted that during the program, the service users developed relationships with services or providers, which may have facilitated movements between levels. All five programs were associated with reduced suicide incidence among women in the target groups or communities. Two programs were also associated with a reduction among men. The study authors speculated that women were more likely to accept services than men, and that the care provided in some studies did less to address issues that are more likely to affect men, such as suicidal impulsivity. We therefore suggest that it is important to build relationships between levels, especially between selective and indicated prevention interventions, but that these can be both formal and informal. Additionally, to reach older men, it may be important to create systematic methods to involve mental health professionals in the indicated prevention intervention. Universal interventions, especially in conjunction with systematically linked indicated and selective interventions, can help to disseminate the benefits across the community.